The Influence of Social Media on Public Policy and Geopolitics-Geostrategy of the State - Deasy Indriani (Novateur Publications, 2022)
The government has just passed the Job Creation Law No. 11 of 2020. Some fundamental changes are in the Post, Telecommunications and Broadcasting sectors. This sector is very strategic when Indonesia enters the industrial revolution 4.0. especially for public policy. This law also requires quality internet services that can be enjoyed by Netizens in the digital era. From a geopolitical perspective, digital sovereignty is very vital. In conventional times, open military and non-military wars focus on the struggle for natural resources in the fields of energy, mining and territory. In the digital era, geopolitics has shifted to the struggle for Big Data and cyber warfare. Like South Korea with the advancement of ICT, taking advantage of the momentum of digitalization as soft diplomacy, foreign policy with creative industries. Intended for cultural propaganda, attitudes to state policies.
Keywords: Industrial Revolution 4.0, Social Media, Geopolitics and Geostrategy Policy i